Stereoselective Synthesis of Novel 2-Alkenyl-2,3,4,5-tetrahydro-1,4-epoxy-1-benzazepines and 2-Alkenyl-2,3,4,5-tetrahydro-1H-1-benzazepin-4-ols - Acosta Quintero, Lina María; Palma, Alirio; Nogueras, Manuel; Cobo, Justo (Synthesis, 2012)
New series of polyfunctionalized 2,3,4,5-tetrahydro-1,4-epoxy-1-benzazepines and 2,3,4,5-tetrahydro-1H-1-benzazepin-4-ols substituted at C2 with 2-methylprop-1-enyl, (E)-styryl, and (E)-pent-1-enyl were synthesized starting from the corresponding N-alkenyl-substituted [prenyl, trans-cinnamyl, (E)-hex-2-enyl] 2-allylanilines by a three-step sequence consisting of selective oxidation of aromatic secondary amines, intramolecular nitrone–olefin 1,3-dipolar cycloaddition, and reductive cleavage. The intramolecular 1,3-dipolar cycloaddition is stereoselective favoring the exo-cycloadducts (ratio exo/endo 2–3:1). The stereochemistry was determined by exhaustive NMR analysis and X-ray diffraction.
Keywords: 1,3-dipolar cycloaddition; 2,3,4,5-tetrahydro-1,4-epoxy-1-benzazepines; 2,3,4,5-tetrahydro-1H-1-benzazepin-4-ols; reductive cleavage; nitrogen heterocycles